GENERALIZED DIFFERENCE SEQUENCE SPACES DEFINED BY A SEQUENCE OF MODULI - Zeren, Suzan; Bektas, Cigdem A. (Univ Kragujevac, Fac Science, 2012)
In this paper, we introduce and study the new sequence spaces [V, lambda, F, p, q, u](0) (Delta(m)(upsilon)), [V, lambda, F, p, q, u] (Delta(m)(upsilon)) and [V, lambda, F, p, q, u](infinity) (Delta(m)(upsilon)) which are generalized difference sequence spaces defined by a sequence of moduli in a locally convex Haussdorff topological linear space X whose topology is determined by a finite set Q of continuous seminorms q. We also study various algebraic and topological properties of these spaces, and some inclusion relations between these spaces. This study generalizes results of Atici and Bektas [11].
Keywords: Difference sequence spaces; sequence of Moduli; seminorm